(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Sharp force injuries are the leading cause of death worldwide. Accidental deaths due to sharp force wounds are extremely rare compared to homicide and suicide cases. Therefore, their exact incidence or prevalence is not accurately known. This paper presents an accidental death due to massive blood loss resulting from the sharp cutting of the left femoral artery by glass fragments that impaled the left groin region of a young male. He was allegedly performing a bike stunt under the influence of alcohol. The body was found in a pool of blood, surrounded by multiple glass fragments from a broken alcohol bottle that was lying shattered next to the body. The autopsy revealed a near-total transection of the left femoral artery and significant glass injuries to the skin. Evidence of self-mutilation and scarification in multiple body regions highlighted risky behavior. To determine the circumstances of death in cases of accidental glass injuries, a thorough medico legal investigation, including details of the death scene, post-mortem examination, and chemical analysis of viscera for any intoxicants or stupefying agents, is always necessary.